Does judicial quality matter for firm performance? - Agregado, Josemaria Gabriel V. (Philippine Review of Economics, 2015)
A sound legal environment is said to be good for business to the extent that it protects property rights, enforces contracts, and ensures the consistency of policies. By lowering uncertainty and contracting costs, a better judiciary is expected to encourage business investments. We test if this hypothesis holds in the Philippine setting by examining whether and how judicial quality is significant to firm-level growth. We construct a quantitative measure of judicial quality, a Judicial Quality Index, using principal components analysis on a diagnostic survey data set of judges across 13 regions, and we use this in a regression analysis of firm-level growth using data from micro, small, and medium enterprises across 34 Philippine cities.